PERAN PERSEPSI POLITIK ORGANISASI, KOMITMEN AFEKTIF, KEPUASAN KERJA DAN STRES KERJA TERHADAP KEINGINAN UNTUK KELUAR DENGAN PERSEPSI DUKUNGAN ORGANISASI SEBAGAI MODERATOR (STUDY DI PT PQRS) - Hermawan, Tri; Mas'ud, Fuad; Perdhana, Mirwan Surya (JURNAL BISNIS STRATEGI, 2018)
This study aims at analyzing influences of political perception of organization, affective commitment, work satisfaction and work stress towards employee’s eagerness to drop out with a variable of moderation perception of endorsement of organization. This study was conducted at PT PQRS. Analysis method used in this study was mixed method with the explanatory sequential design. The number of the sample was 157 respondents for closed questionnaire and 3 participants for opened questionnaire. The questionnaire measurement was closed with scale 1-7. In quantitative analysis data analysis used was multiple regression analysis with moderating variable and a help of SPSS 23 program. In qualitative analysis data analysis used was descriptive analysis.In quantitative analysis of examination findings toward hypothesis, it is indicated that the variable of political perception of organization positively affects an eagerness of dropping out, affective commitment affects an eagerness of dropping out negatively, work stress positively affects an eagerness of dropping out and perception of endorsement of organization can moderate correlation between affective commitment and work stress towards an eagerness to drop out yet not between  perception of endorsement of organization and work satisfaction towards employee’s eagerness to drop out.In qualitative analysis gives results that support the results of hypothesis testing where employees reveal the existence of political behavior and work stress is high enough accompanied by the level of affective commitment and job satisfaction which is low so that it gives the impact on the high desire to get out of work. Other results indicate that organizational support can be perceived by employees so that moderation testing that is conducted get support that the desire to get out of work tends to decrease when they perceive organizational support at low levels of affective commitment and the employees’ desire to get out of work tends to decrease when they perceive organizational support at the high level of work stress.